Tax Policy for Emerging Markets : Developing Countries - Zee, Howell (IMF Working Papers; Working Paper, 2000)
This paper discusses important tax policy issues facing developing countries today. It views tax policy from both the macroeconomic perspective, which focuses on broad questions such as the level and composition of tax revenue, and the microeconomic perspective, which focuses on certain design aspects of selected major taxes, such as the personal income tax, the corporate income tax, the value-added tax, excises, and import tariffs. It provides a review of the rote of tax incentives in these countries, and identifies some policy challenges posed by the globalization of the world economy.